Juridical Analysis of Franchise Law in terms of Civil Law Aspects - Setyawan, Gerald Febrian; Urbaniasi, Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
Franchising arises due to the impact of the advancement of the global economic system. In the business world, especially in the world of trade, Indonesia is dominated by trade in goods which is the result of cooperation between Indonesian and foreign entrepreneurs. There are many forms of franchising in our environment, including fast food businesses such as those from outside and within the country such as Mc Donald, KFC, Pizza Hut, Simple RM, Mbok Berek, Mrs. Suharti and many other brands that are familiar to businesses. home furnishings and office furniture such as Ace Hardware and Ikea. In Indonesia, the legal basis governing franchising is basically not listed in the Criminal Code, but is regulated in Government Regulation No. 42 of 2007 concerning Franchising and also in Regulation of the Minister of Trade of the Republic of Indonesia Number 53/M-DAG/PER/8/2012. Basically the franchise agreement is a type of agreement that is born and grows in the community whose arrangements can be seen in the previous explanation, therefore the franchise agreement is classified as an innominate type of agreement. As referred to in Article 3 of Government Regulation No. 42 of 2007 concerning Franchising, basically aspects of intellectual property rights play a very important role in it. The forms of legal protection contained in a franchise can be classified into two types of legal protection, namely protection in the form of preventive and repressive protection, while the forms of sanctions that can be applied are in the form of administrative sanctions, written warnings or can also be subject to revocation of STPW for Franchisor and Franchisee. who violate the provisions. As a social institution in the field of franchising, or what we are more familiar with as franchising, it is certainly not free from all its weaknesses, even so, this system still has various principles of benefit and advantages in it.